Thermal and chemical effects of fuel direct injection on kinetically controlled combustion of alcohol and gasoline fuels. (December 2015) - Tongroon, Manida; Zhao, Hua
Direct fuel injection into hot residual gases is an effective means to promote and control the autoignition timings during controlled autoignition combustion of gasoline engines. In order to understand better the underlying physical and chemical processes involved, a systematic experimental study was carried out on a single-cylinder engine with optical access by means of thermodynamic analysis, high-speed chemiluminescence imaging, and in-cylinder sampling-based gas chromatography and mass spectroscopy measurements. The relative effects of enthalpy of evaporation and gas expansion from direct liquid fuel injection were quantified. Alcohol fuels (methanol and ethanol), gasoline, and primary reference fuels were investigated and clarified. Chemiluminescence imaging and heat release analysis demonstrated the presence of fuel reforming reactions during the recompression stroke. In-cylinder gas speciation measurement showed that the fuel pyrolysis was the dominant process. In addition, exothermic fuel reformation reactions of alcohol resulted in an increase in the gas temperature and produced many intermediate species during negative valve overlap period. As a result, the start of main heat release process of alcohol fuel occurred earlier in the subsequent compression stroke.